Dual-Source CT Angiography of Peripheral Arterial Stents: In Vitro Evaluation of 22 Different Stent Types - Michael Köhler; Matthias C. Burg; Alexander C. Bunck; Walter Heindel; Harald Seifarth; David Maintz (Radiology Research and Practice)
Purpose. To test different peripheral arterial stents using four image reconstruction approaches with respect to lumen visualization, lumen attenuation and image noise in dual-source multidetector row CT (DSCT) in vitro. Methods and Materials. 22 stents (nitinol, steel, cobalt-alloy, tantalum, platinum alloy) were examined in a vessel phantom. All stents were imaged in axial orientation with standard parameters. Image reconstructions were obtained with four different convolution kernels. To evaluate visualization characteristics of the stent, the lumen diameter, intraluminal density and noise were measured. Results. The mean percentage of the visible stent lumen diameter from the nominal stent diameter was 74.5% ± 5.7 for the medium-sharp kernel, 72.8% ± 6.4 for the medium, 70.8% ± 6.4 for the medium-smooth and 67.6% ± 6.6 for the smooth kernel. Mean values of lumen attenuation were 299.7HU ± 127 (medium-sharp), 273.9HU ± 68 (medium), 270.7HU ± 53 (medium-smooth) and 265.8HU ± 43. Mean image noise was: 54.6 ± 6.3, 20.5 ± 1.7, 16.3 ± 1.7, 14.0 ± 2 respectively. Conclusion. Visible stent lumen diameter varies depending on stent type and scan parameters. Lumen diameter visibility increases with the sharpness of the reconstruction kernel. Smoother kernels provide more realistic density measurements inside the stent lumen and less image noise.